IMPACT OF CHANGES IN CULTURE ON LANGUAGE - Rina Devianty (VISION, 2016)
Language is the result of the culture of a society. Any changes to the culture will be imprinted on the language. Changes in cultural patterns that would have an impact on the language. The impact of cultural change nothing positive and nothing negative. To anticipate the impact, the need for a positive attitude from Indonesian users. A positive attitude can be done by means of fostering and developing Indonesian well, meet the rules already established, as well as the use of Indonesian polite, precise, and logical.Keywords: impact, change, culture, language